2019
DOI: 10.1109/lra.2019.2899433
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Control of Spacecraft's Attitude and End-Effector for Space Robots

Abstract: This paper addresses the coordinated control of the spacecraft's attitude and the end-effector pose of a manipulatorequipped space robot. A controller is proposed to simultaneously regulate the spacecraft's attitude, the global center-ofmass (CoM), and the end-effector pose. The control is based on a triangular actuation decomposition that decouples the endeffector task from the spacecraft's force actuator, increasing fuel efficiency. The strategy is validated in hardware using a robotic motion simulator compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 12 publications
0
42
0
Order By: Relevance
“…Furthermore, the experiments confirmed that in the pre-contact phase the control is realized without any use of thrusters, whereas in the post-contact phase the thrusters are automatically activated to restore the proper inertial location of the system and to dump the angular momentum injected by the impulse. This minimalistic use of the thrusters is the main advantage of the proposed method and leads to reduced fuel consumption and improved performance, as preliminary observed in [30], and further analyzed in Section 6.…”
Section: Discussion Of the Experimental Results And Limitationsmentioning
confidence: 68%
See 4 more Smart Citations
“…Furthermore, the experiments confirmed that in the pre-contact phase the control is realized without any use of thrusters, whereas in the post-contact phase the thrusters are automatically activated to restore the proper inertial location of the system and to dump the angular momentum injected by the impulse. This minimalistic use of the thrusters is the main advantage of the proposed method and leads to reduced fuel consumption and improved performance, as preliminary observed in [30], and further analyzed in Section 6.…”
Section: Discussion Of the Experimental Results And Limitationsmentioning
confidence: 68%
“…For orientation, the vector part of the error quaternion is used [36]. The exact expressions ofx c ,x e ,x b , Jx e , and Jx b can be found in [30,Sect.IV].…”
Section: Coordinated Controlmentioning
confidence: 99%
See 3 more Smart Citations